Response of rabi onion (Allium cepa) to biofertilizers in a sandy loam alluvial soil - Tinna, Diksha; Garg, Naveen; Pandove, Gulab; Sharma, Sandeep; Chawla, Neena; Dhatt, Ajmer Singh (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted in a factorial randomized block design during rabi 2016-18 at Ludhiana. There were 14 treatments consisting of two factors. Factor I comprised two levels of inorganic fertilizers [100% RDF (recommended dose of inorganic fertilizers) and 75% RDF] and factor II consisted of six combinations of biofertilizers along with a control. The data pooled over years revealed that the utilization of various biofertilizers significantly improved the plant height, number of leaves, 20-bulb weight, bulb equatorial diameter and yield over control at both levels of inorganic fertilizers. However, the per cent increase over their respective control was higher when these biofertilizers were used with 75% RDF than with 100% RDF. Biofertilizer treatments significantly improved the ascorbic acid, total soluble solids and pyruvic acid of bulbs, reduced the physiological loss in bulb weight during storage but the differences in bulb dry matter and ash content were non-significant. The effects of all biofertilizers on soil chemical and microbiological properties were beneficial but non-significant. Two treatments, i.e. 100% RDF + T6 (Azotobacter + Sphingobacterium + Burkholderia) and 100% RDF + T1 (Azotobacter + Bacillus) that exhibited 11.5% and 8.6% increment in bulb yield over control (100% RDF) have been identified. Besides, three treatments, i.e. 75% RDF + T6, 75% RDF + T1 and 75% RDF + T5 (Azotobacter + Bacillus + Burkholderia) registered 8.3%, 7.8% and 7.3% higher bulb yield over control (100% RDF) and therefore may be recommended to save 25% inorganic fertilizers.